Prevalence and Determiners of Health Literacy in Turkey (Turkey Health Literacy Journal, 2020)
Aims: The limited level of health literacy (HL) is one of the important issues in Turkey. The validity of HLS EU questionnaire was tested in Turkey in 2012, but it was not applied to identify the HL level. It is necessary to identify our society’s level and eliminate the negativities of insufficient HL. For HL, a great duty falls to the primary healthcare workers which are in close relationship with the public. It was aimed in the study to evaluate the HL level of individuals above 18 years old who applied to primary healthcare centres in the capital city of Turkey. This is the first study for determining the HL level with a scale of which validity had been tested in Turkey and purports to be the pilot of the research concerning the determination of HL level by using the HLS-EU all over the country Methods; In the cross-sectional type research, 2139 individuals were accessed. The questionnaire constructed four levels of HL: insufficient, problematic, sufficient and excellent. Results: Almost 3 in 4 (73,5%) have limited (insufficient/problematic) HL level. According to bivariate correlations and multivariate linear regression model, Limited HL scores were significantly associated with older age, low educational and economic level. Conclusion: The fact that limited health literacy is more widespread in health promotion than in the therapeutic services reveals the importance of initiatives in the field of health promotion.